(untitled) (Research, Society and Development, 2024)
Objective: To describe the main gestational complications presented by pregnant women living with HIV/AIDS. Methodology: This is an integrative, descriptive literature review study, constructed from a scientific database (PubMed, Scielo and Virtual Health Library - VHL). Inclusion criteria were considered: studies related to the consequences/complications of pregnant women living with HIV, available in free full text, published between 2018 and 2022. Excluded were: duplicate works, outside the period in question, with full text unavailable and inappropriate after reading. Results: After adequate screening of the 736 articles found, 11 studies were selected for analysis. These were arranged in a table with year, title, authors, objectives and main results. Its critical analysis allowed us to understand complications associated with HIV in pregnant women, such as: maternal mortality, fetal mortality, low neonatal birth weight, premature birth, increased risk of cesarean section, among others. Conclusion: It was found that such complications make the presence of infection during pregnancy a public health problem, which requires adequate prenatal care in order to avoid such complications for mother and baby.